Trends in incidence and mortality of lung cancer in Switzerland: Possible explanations and open questions. (October 2022) - Frisone, Daniele; Sandoval, Jose; Friedlaender, Alex; Olivier, Timothée; Addeo, Alfredo
Abstract: Background: Using US population-level data, it has been suggested that novel treatment advances, particularly targeted therapies, have contributed to a sharp fall in NSCLC mortality. Switzerland is a high-income country, with a universal, highly performant health care system, easy access to novel drugs but with different dynamics concerning the smoking epidemic than the US. Methods: We use population-based data from Swiss cancer registries to analyze the trends in incidence, mortality and survival and relate them to recent drug approvals. Results: The incidence of NSCLC and SCLC was stable from 1980 to 2018. We noted an important difference between sexes, with an important decrease in men and increase in women, especially for NSCLC. 1-y and 5-y survival have improved for NSCLC between 2004 and 2008 and 2014–2018. Conclusion: These findings should be regarded as the results of a multifactorial improvement in care and it is difficult for us to pinpoint a unique cause explaining the reduction in mortality Highlights: Lung cancer incidence in Switzerland is stable since 1980, with gender differences. Smoking habits are stable since 2011, with a higher prevalence than in the US or UK. Mortality is substantially decreasing, especially in men. 5-year survival for NSCLC increased both in men and women in the last 20 years.